Understanding Iodine Chemistry Over the Northern and Equatorial Indian Ocean. Issue 14 (18th July 2019) - Mahajan, Anoop S.; Tinel, Liselotte; Sarkar, Amit; Chance, Rosie; Carpenter, Lucy J.; Hulswar, Shrivardhan; Mali, Prithviraj; Prakash, Satya; Vinayachandran, P. N.
Abstract: Observations of halogen oxides, ozone, meteorological parameters, and physical and biogeochemical water column measurements were made in the Indian Ocean and its marine boundary layer as a part of the Second International Indian Ocean Expedition (IIOE‐2). The expedition took place on board the oceanographic research vessel Sagar Nidhi during 4–22 December 2015 from Goa, India, to Port Louis, Mauritius. Observations of mixed layer depth, averaged temperature, salinity, and nitrate concentrations were used to calculate predicted iodide concentrations in the seawater. The inorganic iodine ocean‐atmosphere flux (hypoiodous acid [HOI] and molecular iodine [I2 ]) was computed using the predicted iodide concentrations, measured atmospheric ozone, and wind speed. Iodine oxide (IO) mixing ratios peaked at 0.47 ± 0.29 pptv (parts per trillion by volume) in the remote open ocean environment. The estimated iodide concentrations and HOI and I2 fluxes peaked at 200/500 nM, 410/680 nmol·m −2 ·day −1, and 20/80 nmol·m −2 ·day −1, respectively, depending on the parameterization used. The calculated fluxes for HOI and I2 were higher closer to the Indian subcontinent; however, atmospheric IO was only observed above the detection limit in the remote open ocean environment. We use NO2 observations to show that titration of IO by NO2 is the main reason for this result. These observations show that inorganic iodine fluxes and atmospheric IO show similar trends in the Indian Ocean marine boundary layer, but the impact of inorganic iodine emissions on iodine chemistry is buffered in elevated NO x environments, even though the estimated oceanic iodine fluxes are higher. Key Points: NO x titration buffers atmospheric concentrations of iodine oxide Fluxes of inorganic iodine determine iodine oxide levels outside elevated NO x regions A strong gradient in iodine chemistry is observed from close to the coast toward the remote ocean environment